New Insight in The Molecular Mechanisms of Neurodegenerative Disease - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2018)
BACKGROUND: Redox and proteotoxic stress contributes to age-dependent accumulation of dysfunctional mitochondria and protein aggregates, and is associated with neurodegeneration. The free radical theory of aging inspired many studies using reactive species scavengers such as alpha-tocopherol, ascorbate and coenzyme-Q to suppress the initiation of oxidative stress. However, clinical trials have had limited success in the treatment of neurodegenerative diseases (NDDs).CONTENT: The misfolding and aggregation of specific proteins is a seminal occurrence in a remarkable variety of NDDs. In Alzheimer’s disease, the two principal aggregating proteins are β-amyloid (Aβ) and tau. The abnormal assemblies formed by conformational variants of these proteins range in size from small oligomers to the characteristic lesions that are visible by optica lmicroscopy, such as senile plaques and neurofibrillary tangles. Pathologic similarities with prion disease suggest that the formation and spread of these proteinaceous lesions might involve a common molecular mechanism, corruptive protein templating. The accumulation of redox modified proteins or organelles cannot be reversed by oxidant intercepting antioxidants and must then be removed by alternative mechanisms. Autophagy serves this essential function in removing damaged or dysfunctional proteins and organelles thus preserving neuronal function and survival.SUMMARY: Senescent cells and their senescence-associated secretory phenotypes (SASPs) may constitute a novel, understudied, and potentially important contributor to neuro-inflammation and subsequent neurodegeneration. Characterization of cellular senescence in the brain could uncover novel therapeutic targets for the prevention and treatment of chronic age-related NDDs.KEYWORDS: brain, aging, neurodegeneration, DNA damage, senescence, neuro-inflammation, mitochondria, lysosome, proteostasis, prion, amyloidosis